Systematic analysis of barrier‐forming FG hydrogels from Xenopus nuclear pore complexes. (30th November 2012) - Labokha, Aksana A; Gradmann, Sabine; Frey, Steffen; Hülsmann, Bastian B; Urlaub, Henning; Baldus, Marc; Görlich, Dirk
Abstract : Nuclear pore complexes (NPCs) control the traffic between cell nucleus and cytoplasm. While facilitating translocation of nuclear transport receptors (NTRs) and NTR·cargo complexes, they suppress passive passage of macromolecules ⩾30 kDa. Previously, we reconstituted the NPC barrier as hydrogels comprising S. cerevisiae FG domains. We now studied FG domains from 10 Xenopus nucleoporins and found that all of them form hydrogels. Related domains with low FG motif density also substantially contribute to the NPC‧s hydrogel mass. We characterized all these hydrogels and observed the strictest sieving effect for the Nup98‐derived hydrogel. It fully blocks entry of GFP‐sized inert objects, permits facilitated entry of the small NTR NTF2, but arrests importin β‐type NTRs at its surface. O‐GlcNAc modification of the Nup98 FG domain prevented this arrest and allowed also large NTR·cargo complexes to enter. Solid‐state NMR spectroscopy revealed that the O‐GlcNAc‐modified Nup98 gel lacks amyloid‐like β‐structures that dominate the rigid regions in the S. cerevisiae Nsp1 FG hydrogel. This suggests that FG hydrogels can assemble through different structural principles and yet acquire the same NPC‐like permeability. Abstract : The phenylalanine‐glycine (FG) domains of vertebrate nucleoporins assemble into hydrogels with different sieving characteristics for macromolecules. Nup98 forms the tightest filter, which is relieved by O‐linked glycosylation.